1993
DOI: 10.1097/00132586-199304000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Aminopyrine Breath Test in the Prognostic Evaluation of Patients with Cirrhosis

Abstract: This prospective study assessed the role of aminopyrine breath test in the prognosis of patients with cirrhosis, and evaluated whether the test provided useful information not included in the Pugh score. During a period of 36 months, 125 patients with biopsy proven liver cirrhosis were included, and followed for up to 48 months (median 17 months). During follow up 43 patients died (20 of liver failure). Survival was univariately related to aminopyrine breath test (p<002), Pugh score (p<0.01), presence of ascit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 4 publications
(4 reference statements)
4
29
0
2
Order By: Relevance
“…In these cases, 13 C-ABT has been demonstrated to reliably predict histological severity, clinical improvement and short-term survival more than conventional liver function tests. Similarly, in patients with cirrhosis, the addition of 13 C-ABT significantly improved the prognostic stratification of the MELD and Child-Pugh score and, therefore, the estimation of the outcome of the disease [32][33][34]. In patients with HCV-related chronic liver disease, 13 C-ABT has been demonstrated to be useful to evaluate only the severity of disease but not the risk of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, 13 C-ABT has been demonstrated to reliably predict histological severity, clinical improvement and short-term survival more than conventional liver function tests. Similarly, in patients with cirrhosis, the addition of 13 C-ABT significantly improved the prognostic stratification of the MELD and Child-Pugh score and, therefore, the estimation of the outcome of the disease [32][33][34]. In patients with HCV-related chronic liver disease, 13 C-ABT has been demonstrated to be useful to evaluate only the severity of disease but not the risk of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study fulfilled all quality criteria [39]. Thirty-one studies met our criteria for a 'good' quality study [32,37,39,47,55,57,60,62,63,66,76,81,85,89,92,[95][96][97]100,103,104,112,116,117,123,124,128,130,138,142,143]. …”
Section: Description Of Studiesmentioning
confidence: 99%
“…Interestingly, the prognostic information provided by the addition of different markers of liver metabolism (such as the elimination of galactose, ICG, aminopyrine, or lidocaine) to the variables of Child-Pugh score is limited [23][24][25][26]. Similarly, the addition of usual anthropometric markers of nutritional status does not seem to add much to the predictive value of Child-Pugh score [4].…”
Section: Validationmentioning
confidence: 99%
“…For instance, the weight of creatinine is more than twice as high as that of bilirubin in MELD score [32]. Other studies have shown that markers of portal hypertension including oesophageal varices [34], portal blood velocity [35] and hepatic venous pressure gradient [24] provide additional prognostic information when added to the variables of Child-Pugh score.…”
Section: Limitationsmentioning
confidence: 99%